ANALISIS KINERJA KEUANGAN TERHADAP RETURN SAHAM PERBANKAN YANG LISTING DI BURSA EFEK INDONESIA PERIODE 2011-2014 - Nikmatul Maskuroh (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2018)
This research aims to test about the financial performance ratios, namely DER, ROA, EPS, Firm Size, and PBV to the Banking Company shares in the Indonesia Stock Exchange Period 2011-2014. This study uses 25 research objects of Banking Companies listed on the Indonesia Stock Exchange with a 4 year study period that resulted in 100 samples. The results showed of goodness of fit that the fit is perfect. In the hypothesis test using LISREL software is obtained by looking at the t-value to see the effect of variables and determine the significance of the look coefficient on standarized solution. The results show the value of DER 0.181 < 1.96 thus directly DER no effect on stock returns, the value of ROA -1.556 < 1.96 thus directly ROA no effect on stock returns, the value of EPS 1.942 < 1.96 so that EPS does not directly affect the stock return, the value of Firm Size -2.813 > 1.96 thus directly Firm Size effect on stock returns and the value of PBV 3.834 > 1.96 PBV thus directly affect the stock return. Meanwhile, if viewed from the indirect effects of exogenous variables on endogenous variables through an intervening variable the result is: the value of DER 1.262 < 1.96, so that indirectly DER no effect on stock returns through the PBV, the value of ROA 3.253 > 1.96 so that no ROA direct effect on stock returns through the PBV, and the value of EPS 0.436 < 1.96, so that indirectly EPS has no effect on stock returns through the PBV, the value of Firm Size 0.088 < 1.96, so that indirectly Firm Size does not affect the stock returns through the PBV. As a suggestion, the researchers recommend further research to further develop similar research with financial ratios are more varied so as to inform potential investors, financial ratios anything what is good to note that a refund / return through dividends divided by the company or of a capital gain is pretty. In addition to the many studies that developed it is expected that a theory is directly proportional to the results of research.